Surges of the Pamir glaciers in 2020 - V. M. Kotlyakov (Lëd i Sneg, 2021)
Every year, about ten glaciers in the Western Pamirs are in the active stage of movement. The time from the beginning of the movement of kinematic waves along the glacier to the full completion of the pulsation takes, as a rule, 1– 2 years, and in some cases lasts up to 5 years. Activity of the Pamir glaciers in 2020 is discussed in this paper, and we suppose that some pulsations are still in progress in the following years. Data from a number of automatic satellite instruments were used for the analysis, but mainly these were obtained from the International Space Station. In 2020, 10 glaciers in the basins of the Surkhob, Muksu, Seldara, Kyzylsu and Vanch rivers became more active, and in some cases surged. Similar dynamic instability of glaciers was also characteristic for the preceding four years. At present, several major surges are taking place in the Western Pamirs; the Byrs, Vali, Lenin, and Medvezhy glaciers started the active phase of their developments. Therefore, it is necessary to study them by field methods and continue permanent monitoring of them from automatic satellites and the International Space Station.